Study of Technical and Non-technical Factors in Energy Consumption on 20 kV Distribution Networks - Pamungkas, Mikael Abimanyu Putra; Priharto, Dwi; Putranto, Hari (Frontier Energy System and Power Engineering, 2019)
This research aimed to find the technical and non-technical losses that occurred on the 20 kV Tawangrejo Feeder network by calculating the electricity losses after measurement and the calculated losses, made an application to calculate the losses, and determined the improvement alternative from the suitable electricity losses. Based on the data analysis, the conclusions were: Tawangrejo Feeder used mesh configuration with a three-phase four-wire construction model. The values of power and energy losses in total, technical, and non-technical were fluctuating, depended on the current value that was sent from the primary substation to the load. This power loss calculation application had a high accuracy because the error occurred at a maximum of 0.0021%. The most effective power loss improvement was replacing the conductor duct that reduces 56% of power and energy losses.